Optical delay beyond the time-bandwidth limit: From pipe dream to reality - Schulz, S.A.; Grassani, D.; Cardea, I.; Fabbri, S.J.; Upham, J.; Boyd, R.W.; K. L. Tsakmakidis; Bres, C.-S. (International Conference on Transparent Optical Networks, 2019)
All resonant systems throughout science and engineering, independent of their physical implementation have a bandwidth that is inversely related to the decay time. A similar relation exists in all slow-light systems, where the group index (and therefore the delay for a given footprint) is inversely related to the bandwidth. Therefore, resonant or slow-light systems can either store a broad signal for a short time, or a narrow signal for a long time, but cannot achieve large delay for broad bandwidth signals.Here we discuss our recent work on non-reciprocal optical systems that are not constrained by the delay-bandwidth limit. We show that large, broadband optical delay is not a pipe dream and is achievable with current optical technology. We discuss the underlying physics of delay and bandwidth in non-reciprocal optical systems and present an experimental implementation, based on a figure-9 cavity. We demonstrate a delay-bandwidth product 30 times above the seemingly fundamental time-bandwidth limit of traditional systems. Furthermore, we show that the optical pulse can be released after an arbitrary number of round trips, providing the control and tunability lacking from conventional spiral waveguide or fibre loop delay lines. © 2019 IEEE.